2010
DOI: 10.1016/j.numecd.2009.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and markers for the metabolic syndrome in Australian adolescents

Abstract: Background and aims: Overweight and other risk factors for cardiovascular disease (CVD) as well as their clustering, are increasingly prevalent among adolescents. We examined dietary patterns, CVD risk factors, and the clustering of these risk factors in 1139 14-year-olds living in Western Australia. Methods and results: Usual dietary intake was assessed using a food frequency questionnaire. Two dietary patterns, 'Western' and 'Healthy', were identified using factor analysis. Associations between these dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
124
2
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 30 publications
13
124
2
5
Order By: Relevance
“…Individuals with at least 1 SD were considered to be at high risk for cardiometabolic disease. As some authors suggested [29], the estimation of a CMRS that is based on the sum of age-and sex-adjusted z scores for several metabolic risk factors constitutes a valid tool to use in the identification of children and adolescents at risk for developing cardiovascular disease and type 2 diabetes [30] and [31]. Indeed, the employment of such a score permits summation of all risk factors for an individual, creating an overall score that encompasses that person's cumulative risk and, at the same time and to some extent, accounts for the influence of growth and maturation on cardiovascular risk factors [30].…”
Section: Cardiometabolic Risk Scorementioning
confidence: 99%
“…Individuals with at least 1 SD were considered to be at high risk for cardiometabolic disease. As some authors suggested [29], the estimation of a CMRS that is based on the sum of age-and sex-adjusted z scores for several metabolic risk factors constitutes a valid tool to use in the identification of children and adolescents at risk for developing cardiovascular disease and type 2 diabetes [30] and [31]. Indeed, the employment of such a score permits summation of all risk factors for an individual, creating an overall score that encompasses that person's cumulative risk and, at the same time and to some extent, accounts for the influence of growth and maturation on cardiovascular risk factors [30].…”
Section: Cardiometabolic Risk Scorementioning
confidence: 99%
“…As some authors have suggested [14], the estimation of a metabolic risk score (MRS) based on the sum of age-and-sex adjusted Z-scores of several metabolic risk factors constitutes a valid tool to identify children and adolescents at risk of developing cardiovascular disease and type II diabetes [3,9]. Indeed, this approach allows the summari-zation of the cumulative risk that each of the risk factor provides into a continuous score encompassing the overall risk of each individual, and at the same time it accounts to some extent for the influence of growth and maturation on the cardiovascular risk factors [3].…”
Section: Metabolic Risk Scorementioning
confidence: 99%
“…There is a high prevalence of insulin resistance in obese adolescents (1) ; however, it is also important to investigate the possible role of dietary behaviours in relation to insulin resistance in healthy children and adolescents as well (3) . Identification and modification of potentially unfavourable dietary behaviours might be an easy-to-follow method for improving dietrelated health problems.…”
mentioning
confidence: 99%